Polymorphism in alpha-synuclein oligomers and its implications in toxicity under disease conditions - Yoo, Je Min; Lin, Yuxi; Heo, Yunseok; Lee, Young-Ho (Frontiers in Molecular Biosciences, 2022)
The major hallmark of Parkinson’s disease (PD) is represented by the formation of pathological protein plaques largely consisting of α-synuclein (αSN) amyloid fibrils. Nevertheless, the implications of αSN oligomers in neuronal impairments and disease progression are more importantly highlighted than mature fibrils, as they provoke more detrimental damages in neuronal cells and thereby exacerbate α-synucleinopathy. Interestingly, although generation of oligomeric species under disease conditions is likely correlated to cytotoxicity and different cellular damages, αSN oligomers manifest varying toxicity profiles dependent on the specific environments as well as the shapes and conformations the oligomers adopt. As such, this minireview discusses polymorphism in αSN oligomers and the association of the underlying heterogeneity in regard to toxicity under pathological conditions.